Analisis Faktor-Faktor yang Memengaruhi Tindakan Penggelapan Pajak (Studi Literatur Tahun 2018-2023) - Tjendra, Michelle Jane; Setiawan, Temy; Riswandari, Ernie (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of conducting this research is to (1) elucidate the commonly researched factors in academia and presumed variables influencing tax evasion; (2) explain the phenomena that drive research in the realm of tax evasion; (3) attempt to delineate the relevance of the phenomenon addressed in tax evasion-related research concerning the research timeline. This study adopts a qualitative descriptive research design with a literature review approach. The data used in this research consist of research articles on tax evasion from the period 2018-2023 indexed by Sinta. The research findings indicate that there are a total of 45 factors suspected to influence tax evasion, and the dominant issues/phenomena in tax evasion research from 2018-2023 are those from previous years. Additionally, the researcher identified other issues/phenomena driving tax evasion research from 2018-2023 beyond the existing research articles.